Activity and Stability Boosting of an Oxygen‐Vacancy‐Rich BiVO4 Photoanode by NiFe‐MOFs Thin Layer for Water Oxidation. Issue 3 (17th November 2020) - Pan, Jin‐Bo; Wang, Bing‐Hao; Wang, Jin‐Bo; Ding, Hong‐Zhi; Zhou, Wei; Liu, Xuan; Zhang, Jin‐Rong; Shen, Sheng; Guo, Jun‐Kang; Chen, Lang; Au, Chak‐Tong; Jiang, Li‐Long; et al.
Abstract: The introduction of oxygen vacancies (Ov) has been regarded as an effective method to enhance the catalytic performance of photoanodes in oxygen evolution reaction (OER). However, their stability under highly oxidizing environment is questionable but was rarely studied. Herein, NiFe‐metal–organic framework (NiFe‐MOFs) was conformally coated on oxygen‐vacancy‐rich BiVO4 (Ov‐BiVO4 ) as the protective layer and cocatalyst, forming a core–shell structure with caffeic acid as bridging agent. The as‐synthesized Ov‐BiVO4 @NiFe‐MOFs exhibits enhanced stability and a remarkable photocurrent density of 5.3±0.15 mA cm −2 at 1.23 V (vs. RHE). The reduced coordination number of Ni(Fe)‐O and elevated valence state of Ni(Fe) in NiFe‐MOFs layer greatly bolster OER, and the shifting of oxygen evolution sites from Ov‐BiVO4 to NiFe‐MOFs promotes Ov stabilization. Ovs can be effectively preserved by the coating of a thin NiFe‐MOFs layer, leading to a photoanode of enhanced photocurrent and stability. Abstract : A core–shell Ov‐BiVO4 @NiFe‐MOFs photoanode was constructed via a coordination‐assisted self‐assembly method. A NiFe‐MOFs thin layer acts as protective layer and cocatalyst to shift active sites from oxygen vacancies to NiFe‐MOFs, leading to improved stability and activity for OER. This molecular‐based approach tailors the coordination and electronic structure of active sites and provides mechanistic insights for rational design of photocatalysts.